PENGARUH LIFE REVIEW THERAPY TERHADAP DEPRESI LANSIA DI UNIT PELAKSANA TEKNIS (UPT) PESANGGRAHAN PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) MAJAPAHIT MOJOKERTO - Syarifah Maulina; Nurul Mawaddah; Dwiharini Puspitaningsih (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
Depression one of psychosocial problems at elderly. One method reducing depression in elderlylife review therapy. Purpose of this study was to analyze the effect of life review therapy on depression in elderly.This study usedquasy experiment design method withpretest and postest nonequivalent control group design. Sampling with purposive sampling. Depression level measurement tool using Geriatric Depression Scale. Result of paired t test before and after giving life review therapy in intervention group at pretest with ρvalue of 0,000 or < 0,05 which means that there was decrease depression in elderly at time of lifereview therapy. Before and afterlife review therapy in control group at pretest with ρ value of 0,000 or < 0,05. Difference intervention group and control group with result of independent test sample t test with ρ value of .870 or > 0,05 not significant. There effect of life review therapy on elderly depression UPT Pesanggrahan PMKS Majapahit Mojokerto with ρvalue0,000 or ρ<0,05 but there were no significant differences between intervention group and control group. Can be used as routine activity and expected institution can apply life review therapy routinely order to reduce depression and improve quality life erderly people nursing home.